Whole-Genome Sequences of Two Kazachstania barnettii Strains Isolated from Anthropic Environments. (1st February 2022) - Devillers, Hugo; Sarilar, Véronique; Grondin, Cécile; Sterck, Lieven; Segond, Diego; Jacques, Noémie; Sicard, Delphine; Casaregola, Serge; Tinsley, Colin
Abstract: Recent studies have suggested that species of the Kazachstania genus may be interesting models of yeast domestication. Among these, Kazachstania barnettii has been isolated from various microbially transformed foodstuffs such as sourdough bread and kefir. In the present work, we sequence, assemble, and annotate the complete genomes of two K. barnettii strains: CLIB 433, being one of the two reference strains for K. barnettii that was isolated as a spoilage organism in soft drink, and CLIB 1767, recently isolated from artisan bread-making sourdough. Both assemblies are of high quality with N50 statistics greater than 1.3 Mb and BUSCO score greater than 99%. An extensive comparison of the two obtained genomes revealed very few differences between the two K. barnettii strains, considering both genome structure and gene content. The proposed genome assemblies will constitute valuable references for future comparative genomic, population genomic, or transcriptomic studies of the K. barnettii species.